Macro roles for microRNAs in neurodegenerative diseases - Dipen Rajgor (Non-coding RNA Research, 2018)
Neurodegenerative diseases (NDs) are typically adult-onset progressive disorders that perturb neuronal function, plasticity and health that arise through a host of one or more genetic and/or environmental factors. Over the last decade, numerous studies have shown that mutations in RNA binding proteins and changes in miRNA profiles within the brain are significantly altered during the progression towards NDs – suggesting miRNAs may be one of these contributing factors. Interestingly, the molecular and cellular functions of miRNAs in NDs is largely understudied and could remain a possible avenue for exploring therapeutic treatments for various NDs. In this review, I describe findings which have implicated miRNAs in various NDs and discuss how future studies focused around miRNA-mediated gene silencing could aid in furthering our understanding of maintaining a healthy brain.